Planning an effective communication strategy for tourism information centers (TICs) in managing product information - Ety Setiawati; Chondro Suryono (Journal of Gastro Tourism, 2026)
Linggarjati Village possesses significant historical and natural tourism potential, yet its information dissemination remains sporadic and decentralized. This study analyzes the necessity of a centralized Tourist Information Center (TIC) to bridge the information gap and promote local assets effectively. Using a descriptive analysis method with purposive sampling of 45 respondents, the research identifies a tourist profile dominated by young females (56.5%) and Gen Z (43.5%), who prioritize "coolcations," safety (65.2%), and weather accuracy (63%). Findings indicate that while digital platforms are widely used, 43.5% of tourists visit a physical TIC specifically to verify internet-sourced data. Furthermore, 67.4% prefer interpersonal communication with staff supplemented by visual aids. The study emphasizes a systematic management approach encompassing data collection, analysis, and dissemination synergized across multi-platform media including TikTok, Instagram, and physical brochures. The proposed communication strategy, branded as "Explore Linggarjati: History, Nature, and Hospitality," aims to enhance public trust and empower informed decision-making. Ultimately, a TIC integrated with real-time digital tools and competent personnel is vital for the sustainable tourism development of Linggarjati Village.